2012
DOI: 10.1095/biolreprod.111.093880
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Involvement of Plasmin in Early-Stage Follicle Rupture During Ovulation in Medaka1

Abstract: Until recently, the role of the proteolytic system involving serine proteases in follicle rupture during ovulation in mammalian species has been a subject of controversy. We undertook the present study to examine whether proteases play a role in follicle rupture using the teleost medaka (Oryzias latipes) model. Various serine protease inhibitors, including a specific plasmin inhibitor, drastically reduced the rate of ovulation, as assessed by an in vitro ovulation assay, which was established for the fish. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…In our attempts to identify the proteolytic enzymes responsible for follicle rupture during ovulation, various protease inhibitors were tested in preovulatory follicles using the in vitro ovulation system. Serine protease inhibitors, such as aprotinin, leupeptin, antipain and soybean trypsin inhibitor, and MMP inhibitors, such as EDTA, o-phenanthroline and GM6001, strongly inhibited follicle ovulation in vitro (Ogiwara et al, 2005;Ogiwara et al, 2012), suggesting the involvement of two different proteolytic enzyme systems. Our detailed study demonstrated that the serine protease plasmin plays an indispensable role in follicle rupture during medaka ovulation .…”
Section: Follicle Rupture By Two-step Ecm Hydrolysis Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In our attempts to identify the proteolytic enzymes responsible for follicle rupture during ovulation, various protease inhibitors were tested in preovulatory follicles using the in vitro ovulation system. Serine protease inhibitors, such as aprotinin, leupeptin, antipain and soybean trypsin inhibitor, and MMP inhibitors, such as EDTA, o-phenanthroline and GM6001, strongly inhibited follicle ovulation in vitro (Ogiwara et al, 2005;Ogiwara et al, 2012), suggesting the involvement of two different proteolytic enzyme systems. Our detailed study demonstrated that the serine protease plasmin plays an indispensable role in follicle rupture during medaka ovulation .…”
Section: Follicle Rupture By Two-step Ecm Hydrolysis Mechanismmentioning
confidence: 99%
“…Downloaded From: https://bioone.org/journals/Zoological-Science on 11 Jul 2020 Terms of Use: https://bioone.org/terms-of-use MMPs is required for successful ovulation (Ogiwara et al, 2005;Ogiwara et al, 2012). A significant role of the PA/ plasmin system is unique in fish ovulation because, as described above, recent evidence has argued against an essential role of the proteolytic enzyme system for follicle rupture during ovulation in mammals.…”
Section: Similarities and Differences In Ovulation Between Mammals Anmentioning
confidence: 99%
“…In the past decade, the ECM degradation mechanism that regulates follicle rupture has been explored in the medaka (Ogiwara et al 2005(Ogiwara et al , 2012(Ogiwara et al , 2015. The rupture of follicles in the fish is accomplished by the sequential action of two proteolytic enzyme systems, the urokinase-type plasminogen activator-1 (Plau1)/ plasmin system and the matrix metalloproteinase (MMP) system.…”
Section: Ecm Hydrolysis In Follicle Rupture During Teleost Ovulationmentioning
confidence: 99%
“…Further studies using advanced methods such as differential display, subtraction cDNA library and cDNA microarray may provide a way to identify new genes and factors that play a pivotal role in piscine ovulation. Few comprehensive studies revealed important roles for hydrolytic enzymes and metalloproteinases in follicular rupture leading to ovulation (Ogiwara et al 2005(Ogiwara et al , 2012.…”
Section: -3 Ovulationmentioning
confidence: 99%